Trudne początki jako antecedencje dla dzisiejszego Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The author, an expert on the history of legal teaching at the University of Wroclaw, on the occasion of the 75th anniversary of the establishment of the polish Faculty of Law at the University of Wroclaw, presents his reflections related to its founding and their contemporary antecedents. In a synthetic manner, the author refers to selected challenging events in the history of the Faculty and the people associated with them, which are sometimes not known at all to people currently employed at the Faculty. The author realizes that some of his views may meet with some opposition, but the purpose of this paper is more than to show the history of the Faculty of Law in Wroclaw but to encourage reflection on the subject.
Keywords: 75th anniversary; foundation of the Faculty; University of Wroclaw; Faculty of Law